‘We Don’t Know When to Insert Them’: Misuse of Comma and Full stop among Students in Selected Institutions in Delta State, Nigeria - Oboko, Uche; Onovwiona, Solomon (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
. The paper investigates the misuse of comma and full stop among students of University of Delta, Agbor, Delta State Polytechnic, Ogwashi-Uku, and Dennis Osadebay University, Asaba— all in Delta State, Nigeria. Through a simple random sampling technique, 600 students admitted to the institutions during the 2023/2024 academic session were selected from the three institutions (200 from each). The students chosen were students who offered the Use of English course which is a compulsory course for all students in their first year of study. Data for the study were obtained from answers to structured quiz on punctuation, long essays, examination scripts of the students during their first semester and interview. Data for the study were analysed using the theory of error analysis. Findings reveal that poor knowledge of word classes, phrasal and clausal elements, over generalizations among other factors affect students’ placement of the two punctuation marks. Again, the study reveals the relationship between good knowledge of punctuation marks and effective written communication. The paper recommends that teachers should devise activities and tasks on the rules of punctuation and encourage students to put them into practice both at sentence and discourse levels. Keywords:  punctuation, comma, full stop, error analysis, effective writing